Blood, Poo & Dead Skin : The Things Insects Eat - Owen, Ruth, 1967-; Sachner, Mark J.; Randall, Emma (Tunbridge Wells : Ruby Tuesday Books, 2018)
The lives and habits of insects can be truly incredible. Some, however are so gross you probably won't even want to read about them... Oh.. you do Each book in this new series of 4 is packed with truly unbelievable facts about some of the smallest members of the animal kingdom. From wasps that turn spiders into zombies to help them take care of their larvae, to beetles that repel predators with stinking, poisonous, boiling-hot wind. Perfect for reluctant readers, these books deliver curriculum science in the creepiest, yuckiest way possible!
Includes index
Keywords: Insects -- Juvenile literature; Insects; Juvenile works; Juvenile literature